TRAJANIC TREES: THE DACIAN FOREST ON TRAJAN'S COLUMN. (October 2019) - Fox, Andrew
Abstract : Trajan's Column stands in the centre of Rome as a proud monument to Trajan's triumph over Dacia in the early second century. On its 29 m tall shaft, a helical frieze depicts the events of the two wars which won the province for the Roman Empire. There are 224 trees to be found throughout this relief, 222 of which are native to Dacia. These trees have traditionally been treated as scene dividers and background material to the column's action. This article, which begins by exploring the identification of the trees in previous scholarship, argues that they are in fact crucial to the column's narrative of industry and conquest. The discussion of identification is followed by an examination of the numerous tree-felling scenes on the column as a metaphor for conquest. The article closes with a detailed analysis of contrasting representations of the two leaders on the column, Trajan and Decebalus, one an urban emperor, the other a forest king. By directing attention towards the arboreal population of the column, this article argues that trees cannot be dismissed as mere background detail, but play an active and significant role in the communication of ideas about triumph, imperialism and the conquest of nature. Abstract : La colonna traiana si erge nel centro di Roma quale orgogliosa testimonianza del trionfo di Traiano sulla Dacia agli inizi del II sec. d.C. Un fregio elicoidale rappresenta sui suoi ventinove metri di altezza gli eventi delle due guerre che hanno portato alla conquista della regione e alla sua annessione all'impero romano. Sul rilievo possono essere rintracciati duecentoventiquattro alberi, duecentoventidue dei quali sono pertinenti a specie tipiche della Dacia. Dal punto di vista interpretativo gli alberi sono stati tradizionalmente letti come divisori di scene e allo stesso tempo come sfondi per le vicende narrate sulla colonna. Il presente articolo, che prende le mosse dall'analisi dell'identificazione condotta nella letteratura precedente, sostiene che gli alberi sono di cruciale importanza per la narrazione della conquista descritta nella Colonna Traiana. La discussione sull'identificazione sarà poi seguita da un esame delle numerose scene della colonna in cui gli alberi cadono, venendo queste raffigurazioni lette come metafore della conquista. L'articolo si concluderà poi con un'analisi dettagliata delle rappresentazioni contrastanti dei due leader rappresentati sulla colonna: Traiano e Decebalo, il primo imperatore, legato a una realtà urbana, e l'altro invece re di una realtà non urbana. Attraverso l'analisi rivolta alla popolazione arborea della colonna, questo articolo mira a sottolineare come gli alberi non possano essere considerati come semplici elementi di sfondo, ma che al contrario giocano un ruolo attivo e significativo nella comunicazione delle idee concernenti il trionfo, l'imperialismo e la conquista della natura.